EXAMINING INDONESIA'S ISLAMIC COMMERCIAL BANKS HEALTH STATUS USING THE RBBR METHOD - Puspita Sari, Anggi; Sukardi, Budi (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2023)
The scientific importance of Indonesia's Islamic banks' state is the focus of this study using a strategy based on the Risk-based Bank Rating technique. This quantitative descriptive research analyzes the health of Indonesia's Islamic commercial banks, namely Bank Syariah Indonesia and Bank Muamalat Indonesia, for the years 2019 to 2022, focusing on the degree of bank health as measured by the RBBR approach. The study's data analysis leads to the conclusion that Bank Syariah Indonesia's overall condition is represented by a Composite Rank 2 (PK-2) of 85% in 2019, meaning that it is deemed "Healthy" and capable of withstanding significant negative influences from changes in business conditions and other external factors. However Bank Muamalat Indonesia's overall composite rating (PK3), or "Healthy Enough," corresponds to the bank's evaluation of its health level from 2019 to 2022 using the Risk-based Bank Rating method, which includes indicators of Risk Profile, Good Corporate Governance, Earnings (Rentability), and Capital as a whole.